Basement membrane proteins as a substrate for efficient Trypanosoma brucei differentiation in vitro - Rojas, Federico (PLoS Negl Trop Dis, 2021)
The ability to reproduce the developmental events of trypanosomes that occur in their mammalian host in vitro offers significant potential to assist in understanding of the underlying biology of the process. For example, the transition from bloodstream slender to bloodstream stumpy forms is a quorum-sensing response to the parasite-derived peptidase digestion products of environmental proteins. As an abundant physiological substrate in vivo, we studied the ability of a basement membrane matrix enriched gel (BME) in the culture medium to support differentiation of pleomorphic Trypanosoma brucei to stumpy forms. BME comprises extracellular matrix proteins, which are among the most abundant proteins found in connective tissues in mammals and known substrates of parasite-released peptidases. We previously showed that two of these released peptidases are involved in generating a signal that promotes slender-to-stumpy differentiation. Here, we tested the ability of basement membrane extract to enhance parasite differentiation through its provision of suitable substrates to generate the quorum sensing signal, namely oligopeptides. Our results show that when grown in the presence of BME, T. brucei pleomorphic cells arrest at the G0/1 phase of the cell cycle and express the differentiation marker PAD1, the response being restricted to differentiation-competent parasites. Further, the stumpy forms generated in BME medium are able to efficiently proceed onto the next life cycle stage in vitro, procyclic forms, when incubated with cis-aconitate, further validating the in vitro BME differentiation system. Hence, BME provides a suitable in vitro substrate able to accurately recapitulate physiological parasite differentiation without the use of experimental animals.